Illustrated synopsis of dermatology and sexually transmitted diseases - Khanna, Neena (Elsevier, 2011)
This book is simplified and brief journey through skin diseases, peppered with numerous clinical pictures, illustrations and tables. The main aim of this book is to familiarize the medical student and the general practitioner with the plethora of common skin conditions he is likely to encounter, how to handle them correctly, and not to succumb to the morbid temptation of prescribing steroids.